The global capital flows cycle: Structural drivers and transmission channels - Maurizio Michael Habib; Fabrizio Venditti (European Central Bank (ECB), 2019)
In this paper, we study the effects of structural shocks that influence global risk - the main factor behind a "global capital flows cycle" - and how risk, in turn, is transmitted to capital flows. Our results show that not all the risk shocks driving the global financial cycle have the same effects on capital flows. Changes in global risk caused by pure financial shocks have the largest impact on the global configuration of capital flows, followed by US monetary policy shocks. As regards the transmission of risk to capital flows, we uncover a traditional 'trilemma', as countries more financially open and adopting a strict peg are more sensitive to global risk. This "trilemma" is mainly driven by one category of cross-border flows, "other investment", confirming the importance of cross-border banking loans in the narrative of the global financial cycle.
Keywords: E42; E52; F31; F36; F41; 330; Global financial cycle; capital flows; monetary policy; international spillover; global risk